Analysis of the Vicious Circle of Education and Its Impact on Human Development in Iraq - Hussein, Walaa; Saleh, Lawrence (Journal of Economics and Administrative Sciences, 2025)
This research focuses on the complex relationship between education quality and human development in Iraq for 2005 to 2023, emphasizing how the poor conditions in education set in place a vicious circle restricting national progress. Utilizing both inductive and deductive realms, official data of the Ministries of Education and Planning were analyzed, along with comparative international experiences. Indicators analyzed include school density, student-teacher ratio, lack of infrastructure, and limitations of vocational training for primary, secondary, and vocational educational levels. The results show a constant mismatch between students’ population growth and resource allocation to education, thus summarizing an overcrowded school environment, overworked teachers, and degradation of educational quality. Corruption, insufficient public investments, and governance inefficiencies are also cited as factors aggravating the sector’s underperformance. The study reaffirms that education is an essential determinant of human development indicia and that urgent reforms are needed to invest in educational infrastructure, modern-day teaching methods, and fighting corruption. By documenting the interdependence between education and human development, this work advances evidence-based policy measures to break the original cycle for sustainable development.